Dynamic modelling of limitations on improving leaf CO2 assimilation under fluctuating irradiance. (1st January 2018) - Morales, Alejandro; Kaiser, Elias; Yin, Xinyou; Harbinson, Jeremy; Molenaar, Jaap; Driever, Steven M.; Struik, Paul C.
Abstract: A dynamic model of leaf CO2 assimilation was developed as an extension of the canonical steady‐state model, by adding the effects of energy‐dependent non‐photochemical quenching (qE), chloroplast movement, photoinhibition, regulation of enzyme activity in the Calvin cycle, metabolite concentrations, and dynamic CO2 diffusion. The model was calibrated and tested successfully using published measurements of gas exchange and chlorophyll fluorescence on Arabidopsis thaliana ecotype Col‐0 and several photosynthetic mutants and transformants affecting the regulation of Rubisco activity ( rca‐2 and rwt43 ), non‐photochemical quenching ( npq4‐1 and npq1‐2 ), and sucrose synthesis ( spsa1 ). The potential improvements on CO2 assimilation under fluctuating irradiance that can be achieved by removing the kinetic limitations on the regulation of enzyme activities, electron transport, and stomatal conductance were calculated in silico for different scenarios. The model predicted that the rates of activation of enzymes in the Calvin cycle and stomatal opening were the most limiting (up to 17% improvement) and that effects varied with the frequency of fluctuations. On the other hand, relaxation of qE and chloroplast movement had a strong effect on average low‐irradiance CO2 assimilation (up to 10% improvement). Strong synergies among processes were found, such that removing all kinetic limitations simultaneously resulted in improvements of up to 32%. Abstract : This article presents a new simulation model of dynamic CO2 assimilation at the leaf level that includes processes not considered in previous leaf‐level models of CO2 assimilation such as non‐photochemical quenching or chloroplasts movement. The model was validated with measurements on different photosynthetic mutants of Arabidopsis both under steady‐state and fluctuating light conditions. The model was used to quantify potential improvements in CO2 assimilation under fluctuating light by removing kinetic limitations on different processes (enzyme activation, stomatal opening, non‐photochemical quenching relaxation, chloroplast movement, and photoinhibition), and we discuss how these improvements depend on the frequency of fluctuations and on synergies among processes.